2017
DOI: 10.1631/jzus.b1500296
|View full text |Cite
|
Sign up to set email alerts
|

Effects of astaxanthin on oxidative stress induced by Cu2+ in prostate cells

Abstract: Astaxanthin (AST), a carotenoid molecule extensively found in marine organisms and increasingly used as a dietary supplement, has been reported to have beneficial effects against oxidative stress. In the current paper, the effects of AST on viability of prostate cells were investigated by 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay; cell apoptosis and intracellular reactive oxygen species (ROS) levels were determined by flow cytometry; the mitochondrial membrane potential (MMP) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
12
1
Order By: Relevance
“…Oxidation of lipid peroxidation is one of the most widely reported markers of oxidative stress as a contributor to cancer and MDA is the most frequently studied of these markers. In one study, Meng et al (2017) showed that Cu 2+ -induced intracellular ROS accumulation and increased MDA levels with apoptosis reduced by astaxanthin treatment and this might have a protective effect against Cu 2+ -induced oxidative damage by reducing ROS and MDA levels. Similarly, our results revealed that NOB treatment decreased the MDA level in PC-3 cells compared to the control cells not treated with NOB.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidation of lipid peroxidation is one of the most widely reported markers of oxidative stress as a contributor to cancer and MDA is the most frequently studied of these markers. In one study, Meng et al (2017) showed that Cu 2+ -induced intracellular ROS accumulation and increased MDA levels with apoptosis reduced by astaxanthin treatment and this might have a protective effect against Cu 2+ -induced oxidative damage by reducing ROS and MDA levels. Similarly, our results revealed that NOB treatment decreased the MDA level in PC-3 cells compared to the control cells not treated with NOB.…”
Section: Discussionmentioning
confidence: 99%
“…ROS production and antioxidant defense capability cause oxidative stress. Oxidative stress results in cell damage (Meng, Ni, Yu, Wang, & Shen, 2017). ASX has antioxidant, anti-in ammatory and immunomodulatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…ASX decreased ROS and thereby aborted intrinsic apoptosis by upregulating anti-apoptotic Bcl-2 expression and downregulating pro-apoptotic Bax expression (Wen et al, 2015 (Kavitha, Kowshik, Kishore, Baba, & Nagini, 2013). Meng et al reported ASX treatment is not a clear indicator of protective effects on apoptosis for RWPE-1 or PC-3 cells by Annexin V (Meng et al, 2017).…”
Section: Discussionmentioning
confidence: 99%